Estimations d’erreur pour les problèmes de contact unilatéral avec frottement - Louf, François; Pelle, Jean-Pierre; Combe, Jean-Philippe (European Journal of Computational Mechanics, 2001)
In this paper, we present an error estimator for contact problems involving friction. The use of a bipotential in order to formulate the constitutive relation on the contact zone leads to a very straightforward construction of a constitutive relation error estimator for these problems. The implementation is detailed in the case of two elastic bodies and some 2D-examples are presented. An error indicator allowing to estimate the quality of the numerical solution of the non linear problem is presented.